Petrogenesis of tholeiitic basalts from the Central Atlantic magmatic province as revealed by mineral major and trace elements and Sr isotopes - Marzoli, A.; Jourdan, Fred; Bussy, F.; Chiaradia, M.; Costa, F. (Elsevier BV, 2013)
The petrogenesis of the Kerforne dyke tholeiitic basalts (Brittany, France), the northernmost outcrop of the 200 Ma Central Atlantic magmatic province (CAMP), is constrained by its zoned augite and plagioclase crystals. Augite cores with high Mg/Fe and Cr suggest crystallization from near-primary magmas, with slightly enriched Rare Earth element (REE) patterns. Plagioclase crystals with high-An (An85) rounded cores are MgO- and K-rich, REE-poor, and display 87Sr/86Sr200Ma (0.7058) significantly higher than those of the surrounding ground-mass (0.7052–0.7053) suggesting open-system evolution processes. We propose a differentiation process involving mixing of different mafic magmas which occurred in less than a few hundred years judging from the lack of diffusive re-equilibration of major and trace elements in augite and of 87Sr/86Sr200Ma in plagioclase cores. The relatively large range of incompatible element contents and ratios of observed and calculated magmas are possibly due to fractional crystallization and to moderate amounts of crustal contamination which affected the more primitive magmas in particular. The calculated magmas reach near-primitive compositions and suggest that they originated from melting of a spinel peridotite slightly enriched in LREE vs. HREE.